Consider the following binomials.

A=(x^2+5x) B=(6x+30)

Part 1: Factor each binomial by finding the GCF. Then, add the two factored binomials to make a single expression.

Part 2: Now add the original forms of binomial A and B together to make a trinomial. Factor the trinomial.

Part 3: Do you see something you could do to your answer in Part A to get your answer to Part B? Explain.

I know how to factor the binomials by finding the GCF. But I'm confused in this case for Parts A and B. For B, I think the gcf can be 3 and for A, the GCF can be 5.

1 answer

1. The GCF is x + 5
A = (x+5)x and b = 6(x+5)

2. A + B = x^2 + 11 x + 30 = (x+6)(x+5)

3. Looking at the answer in (1), it can also be written (x+5)(x+6), with the GCF as one of the factors.
Similar Questions
  1. Consider the following binomials.A=(x^2+5x) B=(6x+30) Part 1: Factor each binomial by finding the GCF. Then, add the two
    1. answers icon 1 answer
  2. Consider the following binomials.A=(x^2+5x) B=(6x+30) Part 1: Factor each binomial by finding the GCF. Then, add the two
    1. answers icon 1 answer
    1. answers icon 0 answers
    1. answers icon 1 answer
more similar questions